2015
DOI: 10.1074/mcp.m114.045922
|View full text |Cite
|
Sign up to set email alerts
|

Succinylome Analysis Reveals the Involvement of Lysine Succinylation in Metabolism in Pathogenic Mycobacterium tuberculosis*

Abstract: Mycobacterium tuberculosis (Mtb), the causative agent of human tuberculosis, remains one of the most prevalent human pathogens and a major cause of mortality worldwide. Metabolic network is a central mediator and defining feature of the pathogenicity of Mtb. Increasing evidence suggests that lysine succinylation dynamically regulates enzymes in carbon metabolism in both bacteria and human cells; however, its extent and function in Mtb remain unexplored. Here, we performed a global succinylome analysis of the v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
139
4

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(160 citation statements)
references
References 86 publications
17
139
4
Order By: Relevance
“…A majority of modified proteins are found to be associated with metabolism and are cytosolic. Also, negative regulation of protein function was found in three such studies (88,90,91). Analysis of the mycobacterial acetylome for the presence of other modifications such as pupylation and phosphorylation reveal novel signaling nodes in Mycobacterium.…”
Section: Lysine Acylation In Mycobacteriamentioning
confidence: 99%
“…A majority of modified proteins are found to be associated with metabolism and are cytosolic. Also, negative regulation of protein function was found in three such studies (88,90,91). Analysis of the mycobacterial acetylome for the presence of other modifications such as pupylation and phosphorylation reveal novel signaling nodes in Mycobacterium.…”
Section: Lysine Acylation In Mycobacteriamentioning
confidence: 99%
“…In terms of the multiple differentially expressed protein classification, cluster analysis offered the chance to authenticate the accuracy of potential connections and differences in specific functions, we collected the functional classification information and obtained P ‐values of the protein groups, we screened the functional classification for significant enrichment ( P ‐value <0.05) in at least one cluster. Immediately after, the screened data matrix was transformed by the function x = −log10 ( P value), and then classified by Z ‐transformation.…”
Section: Methodsmentioning
confidence: 99%
“…Subsequently, western blotting analysis was used to identify the lysine succinylated peptides derived from the proteins in vivo. Increasing evidence has revealed that succinylation locating on critical metabolic networks, such as enzyme activity, central metabolism pathway and cell stress response to aging and apoptosis. As a result of the mitochondrial sirtuin SIRT5‐mediated lysine desuccinylation, lysine succinylation sites overlapped to differential extents and regulations compared with other diverse post‐translational modifications.…”
Section: Introductionmentioning
confidence: 99%
“…15,17,33 Furthermore, bacterial acetylome studies have been limited to the analysis of lysine residues. O-acetylation of proteins has been shown to be involved in regulating key functions in eukaryotes.…”
Section: Introductionmentioning
confidence: 99%